Method and system for managing wireless bandwidth resources - Holur, Balaji; Ram Dantu; Derrick, Charles (Cisco Technology Inc, 2009)
A method and system for managing wireless bandwidth resources include the capability to receive at a serving node a service request for a mobile unit and to communicate with a wireless network node to determine whether sufficient wireless bandwidth is available for the requested service. The method and system also include the capability to process the service request based on the availability of wireless bandwidth.
Keywords: data; mobile; node; service; unit

Method and system for providing services for wireless data calls - Ram Dantu; Patel, Pulin; Patel, Pravir; Garbuz, Alexander; Miernik, Jerzy; Patel, Achal; Holur, Balaji (Cisco Technology Inc, 2007)
A method and system for providing services for wireless data calls includes monitoring a wireless data call for a predefined event associated with a service for the wireless data call. The service is initiated for the wireless data call in response to detecting the predefined event for the data call. The predefined event may comprise a uniform resource locator (URL) match or change, excess use of transmission or time resources, a location change of a mobile device for the wireless data call, a network event, or a combination of any or all suitable events.
Keywords: call; data; network; service; wireless

Quality indicator and method for frame selection in wireless network - Alam, Mahbubul; Ram Dantu; Holur, Balaji; Eyceoz, Tugay (Cisco Technology Inc, 2006)
A method and system for indicating quality of a radio frame transmitted over a wireless link includes receiving a radio frame from the wireless link. A power indicator for the radio frame is determined based on a power control trend of the wireless link. A quality indicator for the radio frame is generated based on the power indicator.
Keywords: frame; indicator; link; quality; radio